Advancements in Medical Imaging: The Role of Artificial Intelligence in Enhancing Diagnostic Accuracy - Dhayie, Abbas Kashash; Ktab, Abdullah Hassan; Zayd, Hasanin Eabd Alshahid Eabd; Kamel, Ali Ahmed Mohammed (American Journal of Botany and Bioengineering, 2025)
Medical imaging plays an indispensable role in guiding clinical diagnoses, medical treatment planning, interventional therapy equipment placement, surgical operations, and patient outcomes. Advanced imaging equipment, radiopharmaceuticals, and increasing awareness of available imaging modalities lead to unprecedented data growth, which poses huge pressure on human reading and evaluating capacities. Meanwhile, the required time for each reading varies according to the complexity of the cross-sectional findings, increasing the probability of human error. Furthermore, the critical medical evaluation of the significant loss of life and financial consequences of delayed or misdiagnosed treatment encourages regular and accurate readings. Conversely, radiologists’ job satisfaction and social demands are the foundational supports of high-quality imaging. This review regroups findings based on common features and illuminates the future large-scale medical imaging AI accomplishments to casual researchers.